Agro-morphological characterization of Allium sativum L. cultivars grown under semi-arid conditions - Belagrouz, Abdenour; Bendada, Hocine; Tifouri, Zineb; Tabet Derraz, Farah (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Garlic (Allium sativum L.) is a vegetable and medicinal crop with significant genetic diversity in Mediterranean regions. The valorization of this condiment is necessary to meet production demands. An experiment was conducted at ITCMI of Sidi Bel Abbes, Algeria, to evaluate the variation of agro-morphological properties of 10 garlic cultivars during the 2023/2024 growing season. The morphological evaluation revealed significant variety effects on leaves, bulbs, and cloves. The varieties Rose de Chine, Rouge Local, and Germidour showed important leaf length dimensions (52.79, 53.23 and 52.1 cm) and leaf surface area (97.61, 88.48 and 86.26 cm²), respectively. Regarding bulbs and cloves, the varieties Messidrômes and Mocta Bulgare indicated better performance in weight (54.45 and 6.9 g) and diameter (52.69 and 22.71 mm), respectively. The Fructidor variety had the highest number of cloves per bulb (14.16). These results highlight the potential of selected cultivars for specific end uses: foliage-vigorous varieties for biomass-oriented programs, and high-yielding bulb varieties for commercial production under semi-arid conditions. The identified agro-morphological diversity provides a valuable basis for varietal selection, breeding programs, and the conservation of locally adapted garlic germplasm.